2020
DOI: 10.1108/imefm-11-2018-0407
|View full text |Cite
|
Sign up to set email alerts
|

Organization-stakeholder relationship and performance of Iranian SMEs

Abstract: Purpose This study aims to explore the direct and indirect effects of organizational stakeholder’s relationship on performance through innovativeness and risk-taking among small and medium enterprises (SMEs). Design/methodology/approach This study used the cluster sampling method to select the study sample and the questionnaire survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(62 citation statements)
references
References 79 publications
4
57
0
1
Order By: Relevance
“…According to the data processing results, it was shown that innovation does not have a significant implication on business performance. These results are not in line with (Hallak et al, 2018), (Linton, 2019), (Jalali et al, 2020), (Riassy & Kristinae, 2021). The findings showed that when a pandemic occurs, business conditions experience uncertainty, therefore the market does not consider innovation in making purchasing decisions.…”
Section: Achieving Performancementioning
confidence: 79%
See 4 more Smart Citations
“…According to the data processing results, it was shown that innovation does not have a significant implication on business performance. These results are not in line with (Hallak et al, 2018), (Linton, 2019), (Jalali et al, 2020), (Riassy & Kristinae, 2021). The findings showed that when a pandemic occurs, business conditions experience uncertainty, therefore the market does not consider innovation in making purchasing decisions.…”
Section: Achieving Performancementioning
confidence: 79%
“…This means the entrepreneurs' courage in taking risks will implication business performance. This study showed risk-taking has a significant implication on business performance, which is related to (Linton, 2019), (Jalali et al, 2020), (Soininen & Puumalainen, 2012). According to the data processing results, it was shown that innovation does not have a significant implication on business performance.…”
Section: Achieving Performancementioning
confidence: 80%
See 3 more Smart Citations